Sayyid Abul A'la Mawdudi’s views on ijtihad and their relevance to the contemporary Muslim society - Haque, Munawar (International Islamic University Malaysia, 2010)
The purpose of this article is to explore the views of Sayyid Abul A'la Mawdudi on ijtihad. It intends to trace the origins of Mawdudi’s ideas within the social, cultural and political context of his time. The study will show that Mawdudi’s understanding of ijtihad and its scope demonstrates originality. For Mawdudi, ijtihad is the concept, the process, as well as the mechanism by which the Shariah, as elaborated in the Qur’an and the Sunnah is to be interpreted, developed and kept alive in line with the intellectual, political, economic, legal, technological and moral development of society. The notion of ijtihad adopted by Mawdudi transcends the confines of Fiqh (jurisprudence) and tends, therefore, to unleash the dormant faculties of the Muslim mind to excel in all segments of life. In Islamic legal thought, ijtihad is understood as the effort of the jurist to derive the law on an issue by expending all the available means of interpretation at his disposal and by taking into account all the legal proofs related to the issue. However, its scope is not confined only to legal aspect of Muslim society. Mawdudi’s concept of ijtihad is defined as the legislative process that makes the Islamic legal system dynamic and makes its development and evolution in the changing circumstances possible. This results from a particular type of academic research and intellectual effort, which in the terminology of Islam is called ijtihad. The purpose and object of ijtihad is not to replace the Divine law by man-made law. Its real object is to properly understand the Supreme law and to impart dynamism to the legal system of Islam by keeping it in conformity with the fundamental guidance of the Shariah